Sistema nazionale di istruzione e parità scolastica: aspetti giuridici e pedagogici: aspetti giudirici e pedagogici - Davide Capperucci (Firenze University Press, 2020)
This paper examines the changes introduced in the national education system after private schools obtained offical recognition. Starting from the analysis of the legal aspects that characterize schools which are offically recognized and those which are not according to the Italian legal system, the paper also considers the pedagogical and didactic implications linked to the establishment of a "mixed system" in which several, individual and institutional, public and private, bodies are responsible for the education and training of the younger generations. This plurality of bodies poses the need to ensure the same degree of effectiveness and efficiency of the school service to the entire education system, by identifying well-defined organization performances and learning results, in full respect of cultural, pedagogical, philosophical and confessional differences connected to the various school models existing today.